Enhancing Islamic Boarding School Management in Jombang through Artificial Intelligence - Kurnianingtyas, Diva; Daud, Nathan; Widodo, Agus Wahyu; Muflikhah, Lailil; Yudistira, Novanto (SMONAGENES Research Center, Univeritas Brawijaya, 2025)
The drive for digital transformation and the need to enhance governance efficiency in religious educational institutions provided the backdrop for this community service program, which implemented artificial intelligence (AI) technology at an Islamic boarding school in Jombang. This program aimed to enhance the management competencies of Islamic boarding schools in Jombang by applying AI technology. The activities included socialization and training sessions on AI-based applications such as facial recognition, attendance systems, and student nutrition management tools. A one-group pretest–posttest design was employed to evaluate management competence before and after the training. The analysis showed a significant increase in participants’ scores from the pretest (23.86 ± 3.34) to the posttest (45.06 ± 1.56), with Z = –6.166 and p < 0.001. This improvement contributed to more efficient student attendance tracking, optimized data-based nutrition management, and motivated participants to integrate technology into pesantren administration. The practical implication of this program is the need for continuous training to expand further the adoption of artificial intelligence in other Islamic boarding schools.